Theorizing Practice and Practicing Theory - Feldman, Martha S.; Orlikowski, Wanda J. (Organization Science, 2011)
This paper describes the emerging field of practice theory as it is practiced in relation to organizational phenomena. We identify three approaches—empirical, theoretical, and philosophical—that relate to the what, the how, and the why of using a practice lens. We discuss three principles of the theoretical approach to practice and offer examples of how practice theory has been used in the organizational literature and in our own research. We end with a discussion of the challenges and opportunities that practice theory affords organizational scholarship.